The correlations between body posture parameters and physical fitness characteristics of male and female pupils playing the accordion and the Western concert flute - Mateusz Apanowicz (Kazimierz Wielki University, 2018)
Introduction. The boundaries of human adaptation to the load of exercise in sport, recreational and occupational activity are flexible but not unlimited. Material, methods and research tools. 393 students from randomly selected music schools were qualified for the study. In each of the schools involved in the study, the level of physical fitness was assessed using the Eurofit test and the level of body posture parameters by means of the photogrammetric method. Summary As regards the players of musical instruments, the most frequent correlations with the characteristics of physical fitness were observed among female pupils of class III, IV, V and male pupils of class I, moderately frequent relationships were recorded among female students of II, VI and male students of class II, III and the fewest correlations were noticed among female pupils of class I and male pupils of class IV and V. Considering the frequency of correlations among female students, the most frequent relationships were recorded in class I, V and IV, the moderately frequent ones in class II and VI and the fewest in class I (...)